2018
DOI: 10.1016/j.schres.2017.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable auditory mismatch response and connectivity patterns in adolescents with schizophrenia and adolescents with bipolar disorder with psychosis: A magnetoencephalography study

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…However, if the DNMnet in the brain falls into a more stable state, as in the PD group, the stability may lead to cognitive inflexibility and functional impairments (Serrano-Guerrero et al, 2020). Previous studies reported altered connectivity underlying MMN in psychotic disorders (Dima et al, 2012;Ranlund et al, 2016;Braeutigam et al, 2018). However, MMN does not highlight the dynamical mechanism to clarify its reduction in psychotic disorders.…”
Section: Discussionmentioning
confidence: 97%
“…However, if the DNMnet in the brain falls into a more stable state, as in the PD group, the stability may lead to cognitive inflexibility and functional impairments (Serrano-Guerrero et al, 2020). Previous studies reported altered connectivity underlying MMN in psychotic disorders (Dima et al, 2012;Ranlund et al, 2016;Braeutigam et al, 2018). However, MMN does not highlight the dynamical mechanism to clarify its reduction in psychotic disorders.…”
Section: Discussionmentioning
confidence: 97%
“…This association by latency and approximate source location suggests that DBS influences a cascade of neuronal mechanism related to primary and secondary visual processing, stimulus evaluation and categorization, selective attention, visual working memory, and semantic processing. Evoked amplitudes are reduced in a variety of mental disorders compared to neuro-typical development (Godier et al, 2016 ; Braeutigam et al, 2018 ; Ahtam et al, 2020 ; Hiluy et al, 2021 ; Romero Frausto et al, 2021 ) and DBS may restore a kind of “normality” at the neuronal level. This notion is in line with the hypothesis that electrical neuromodulation shifts abnormal circuits toward a more normative physiological state (Lee et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The MMN is a negative-going peak reflecting the differences between scalp-level ERP responses to deviant vs. standard stimuli measured across a 135-205-ms time window and thought to reflect an automatic deviance detection process. Several studies have reported large effect sizes for MMN differences between schizophrenia patients and controls using electroencephalography (EEG;Hermens et al, 2010;Javitt et al, 1995;Koshiyama et al, 2017Koshiyama et al, , 2018bKoshiyama et al, , 2018cLight and Braff, 2005;Rasser et al, 2011;Salisbury et al, 2017;Wynn et al, 2010) or magnetoencephalography (Braeutigam et al, 2018;Yamasue et al, 2004), and these findings have been confirmed by several meta-analyses (Erickson et al, 2016;Umbricht and Krljes, 2005); These impairments are among the most consistently replicated findings in schizophrenia research (Keshavan et al, 2008;Näätänen et al, 2019). Many studies have also identified important associations between MMN and cognition (Koshiyama et al, 2018c;Rissling et al, 2014;Toyomaki et al, 2008;Wynn et al, 2010), negative symptoms and functional outcomes (Koshiyama et al, 2018c;Light and Braff, 2005;Rissling et al, 2014) in schizophrenia patients.…”
Section: Introductionmentioning
confidence: 89%